State and Social Movements: Identities, Crosses and Strategies in Tension in Latin America (Revista Rupturas, 2021)
This article analyzes the crosses between social movements and State in Latin America. It focuses on a series of tensions in the identities and strategies of social and popular movements and progressive governments: socialist struggle-capitalist relations of production, commodification-decommodification, horizontal participation-vertical representation, articulatory strategies-particularist strategies. In the second part, it analyses the problems of ultra-particularist strategies and binary conceptions and the role of the State in the hegemonic dispute. In the last part, it examines the limits and contradictions of some progressive governments in the region to radicalize and expand participatory democracy, strengthen the modes of communitarian self-management and popular power, promote decommodification and move towards a democratic socialism.
Keywords: State and society; social and popular movements; political identities; hegemonic struggle; radical democracy